Tim-3 pathway dysregulation and targeting in sepsis-induced immunosuppression - Jialiu Luo; Cong Zhang; Deng Chen; Teding Chang; Shunyao Chen; Zhiqiang Lin; Chengla Yi; Zhao-Hui Tang (European Journal of Medical Research)
Abstract Sepsis is a major medical problem which causes millions of deaths worldwide every year. The host immune response in sepsis is characterized by acute inflammation and a simultaneous state of immunosuppression. In the later stage of sepsis, immunosuppression is a crucial factor that increases the susceptibility of septic patients to secondary infection and mortality. It is characterized by T cell exhaustion, excessive production of anti-inflammatory cytokines, hyperproliferation of immune suppressor cells and aberrant expression of immune checkpoint molecules. T cell immunoglobulin and mucin domain 3 (Tim-3), an immune checkpoint molecule, is found on the surface of various cells, including macrophages, NK cells, NKT cells, and T cells. There are four different ligands for Tim-3, and accumulating evidence indicates that Tim-3 and its ligands play a crucial role in regulating immune cell dysfunction during sepsis. Anti-Tim-3 antibodies have been applied in the field of cancer immunotherapy and have achieved positive therapeutic effects in some clinical trials. However, the therapeutic efficacy of Tim-3 blockade is still controversial in animal models of sepsis. These challenges highlight the need for a deeper understanding of Tim-3 signaling in sepsis. This review examines the comprehensive effect of Tim-3 signaling in the development of sepsis-induced immunosuppression and the therapeutic efficacy of Tim-3 blockade.